2022
DOI: 10.1037/xge0000901
|View full text |Cite
|
Sign up to set email alerts
|

Right place, right time: Spatiotemporal predictions guide attention in dynamic visual search.

Abstract: Visual search is a fundamental element of human behavior and is predominantly studied in a laboratory setting using static displays. However, real-life search is often an extended process taking place in dynamic environments. We have designed a dynamic-search task in order to incorporate the temporal dimension into visual search. Using this task, we tested how participants learn and utilize spatiotemporal regularities embedded within the environment to guide performance. Participants searched for eight instanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 71 publications
1
28
1
Order By: Relevance
“…Similar results were reported in a study measuring eye movements to explore spatial orienting in time [84]. Participants performed a search task in which the presentation of targets was spatiotemporally predictable, such that the target appeared in a specific quadrant at a specific time point in time within a trial.…”
Section: More Complex Regularitiessupporting
confidence: 70%
“…Similar results were reported in a study measuring eye movements to explore spatial orienting in time [84]. Participants performed a search task in which the presentation of targets was spatiotemporally predictable, such that the target appeared in a specific quadrant at a specific time point in time within a trial.…”
Section: More Complex Regularitiessupporting
confidence: 70%
“…Yet, a carefully controlled study using dual-task designs has shown that foreperiod effects survive in the face of a simultaneously performed task ( van Lambalgen and Los, 2008 ). In a similar vein, recent work from our lab has revealed that learned (spatio)temporal regularities regarding external events can guide visual-search performance even when interacting with temporally unpredictable intervening events ( Boettcher, Shalev, Wolfe, & Nobre, 2021 ). Likewise, temporal expectations affect performance even during dynamic streams that require inhibition of temporally competing distractors ( Chauvin, Gillebert, Rohenkohl, Humphreys, & Nobre, 2016 ; Davranche, Nazarian, Vidal, & Coull, 2011 ; Zokaei et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…As it might be impossible to design tasks ruling out timing to such variable intervals, they are important to consider in any temporal task. For example, such ‘irregular’ timing might similarly play a role in recent work that found visual search to be facilitated for regular versus irregular spatiotemporal patterns (Boettcher et al, 2022). This performance benefit, expressed as average RT and HR split on regularity, was interpreted to arise from learning the spatiotemporal pattern that guides attention in visual search.…”
Section: Discussionmentioning
confidence: 98%
“…These regularity benefits are commonly interpreted to emerge from the ability to extract regular intervals from the environment (e.g., Baker et al, 2004;Boettcher et al, 2022;Fiser & Aslin, 2001;Salet et al, 2021;Sherman et al, 2020;Zhao et al, 2013). SL's temporal aspects have particularly been studied in temporal variants of the serial reaction time (SRT) tasks (Gobel et al, 2011;Heideman et al, 2018Heideman et al, , 2016Olson & Chun, 2001;O'Reilly et al, 2008;Salidis, 2001;Sanchez et al, 2015;Shin & Ivry, 2002, 2003 In classic SRT tasks (Nissen & Bullemer, 1987), participants make a corresponding keypress to each item in a stimulus sequence (e.g., stimuli A-B-A responded to with index-middle-index finger).…”
Section: Temporal Preparation Drives Statistical Learning Effectsmentioning
confidence: 99%
See 1 more Smart Citation